Around the pole: evolution of sub‐Antarctic Ranunculus. (15th February 2017) - Lehnebach, Carlos A.; Winkworth, Richard C.; Becker, Matthias; Lockhart, Peter J.; Hennion, Françoise
Abstract: Aim: Despite an improved understanding of Southern Hemisphere plant biogeography, the origins and evolution of sub‐Antarctic floras remain poorly studied. Here, we investigate the historical biogeography of sub‐Antarctic representatives of the genus Ranunculus . We aimed to establish when and from where the sub‐Antarctic ranunculi originated as well as to examine the extent to which ecomorphological traits explain contemporary biogeographical patterns. Location: Southern temperate and sub‐Antarctic zones. Methods: We first estimated a dated phylogeny for Ranunculus using combined chloroplast and nuclear data for 53 accessions; divergence times were inferred based on three temporal calibrations. We then used non‐parametric multidimensional scaling to evaluate the ecomorphological diversity of 67 austral ranunculi representing a combination of sub‐Antarctic species and those restricted to lower latitude landmasses. Results: Phylogenetic analyses indicated that several Ranunculus lineages have colonized the sub‐Antarctic islands. Divergence time estimates suggest recent arrival from source areas in Australia, New Zealand or South America. Species exhibiting two distinct ecomorphological trait combinations occur in both sub‐Antarctic and lower latitude habitats; the proportions of each combination differed significantly between these areas. Main conclusions: Ranunculus has colonized the sub‐Antarctic on several occasions, most often arriving from the lower latitude landmasses prior to the Last Glacial Maximum. Taken together our analyses suggest that chance effects are likely to have influenced species arrival. However, following arrival trait–environment interactions appear to have been important for the subsequent establishment and persistence of ranunculi in sub‐Antarctic habitats.